2000
DOI: 10.3109/10611860008996861
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein as a Carrier of Cytostatics in Cancer Chemotherapy: Study of Stability of Drug-carrier Complexes in Blood

Abstract: Several solid tumour and leukemia cell types have a higher low density lipoprotein (LDL) uptake than the corresponding normal cells. We are investigating the possibilities to use LDL as a drug carrier to increase the selectivity of antineoplastic drugs in cancer chemotherapy. We have developed a method to incorporate lipophilic cytotoxic agents without interfering with the in vitro and in vivo properties of LDL. In this study, we examined the stability of some drug-LDL complexes in blood and plasma as this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
0
14
0
5
Order By: Relevance
“…Такой подход описан в литературе для повышения доставки некоторых лекарств, в частности, противоопухолевых -за счёт их связывания с липопротеинами низкой плотности (ЛНП) [6][7][8]. Это может быть в принципе применено и для противотуберкулёзных препаратов, в частности, для рифампицина.…”
unclassified
See 1 more Smart Citation
“…Такой подход описан в литературе для повышения доставки некоторых лекарств, в частности, противоопухолевых -за счёт их связывания с липопротеинами низкой плотности (ЛНП) [6][7][8]. Это может быть в принципе применено и для противотуберкулёзных препаратов, в частности, для рифампицина.…”
unclassified
“…В частности, полагают возможность совместного транспорта с помощью этих белков липофильного лекарства вместе с фосфолипидами из частицы-переносчика к ЛВП или/и вместе с этерифицированным холестерином из ЛВП к ЛОНП и ЛНП [17]. В большинстве случаев такое перераспределение лекарств, например, противоопухолевых и противовоспалительных, сопровождается повышением их фармакологической эффективности за счёт появления возможности рецепторного взаимодействия с клеткой-мишенью [7,16]. Для рифампицина имеются лишь данные о его ассоциации с альфа-1-кислым гликопротеином, причём показано, что у больных туберкулёзом она может увеличиться за счёт гликозилирования белка [18].…”
unclassified
“…10 The use of a solid lipid nanoparticle system as a methotrexate carrier was reportedly shown to improve drug pharmacokinetics and to achieve regression of Ehrlich ascites carcinoma in mice. 11,12 The demonstration by Ho et al 13 that low-density lipoprotein receptors are overexpressed in neoplastic cells, paved the way for the use of lipoproteins [14][15][16][17] and subsequently of lipoprotein-like nanoemulsions 18,19 as vehicles to concentrate chemotherapeutic agents in neoplastic tissues. Taking this approach, the low-density lipoprotein receptor-mediated endocytic pathway is used to internalize drug-loaded lipid particles.…”
Section: Introductionmentioning
confidence: 99%
“…Taking this approach, the low-density lipoprotein receptor-mediated endocytic pathway is used to internalize drug-loaded lipid particles. [14][15][16][17] We showed that cholesterol-rich nanoemulsions, with a lipid structure mimicking low-density lipoprotein, has the ability to bind to low-density lipoprotein receptors. A lipid nanoemulsion is made without protein but, in contact with plasma, acquires apolipoprotein E, which is recognized by low-density lipoprotein receptors.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de LDL como agente direcionador de fármacos para as células neoplásicas tem sido explorado desde meados dos anos 1980 por diversos grupos (Rudling et al, 1983;Tokui et al, 1995;De Smidt & Van Berkel, 1990;Lundberg, 1987;Samadi-Baboli et al, 1993;Xiao et al, 1999) (De Smidt & Van Berkel, 1990 Atualmente existem vários estudos sobre a associação bem sucedida de antineoplásicos à LDL, dentre os quais se destacam a doxorrubicina (Chu et al, 2001;Kader et al, 1998), os derivados lipofílicos da daunorrubicina (Verluis et al, 1996) e os derivados lipofilícos da adriamicina (Masquelier et al, 2000). Também já foi demonstrada a incorporação de radiofármaco hidrofóbico marcado com I 125 captado pelos rLDL em três linhagens de tumores cervicais humanos (Xiao et al, 1999 Mesmo sem conter a proteína da LDL, a LDE entra em contato com as lipoproteínas naturais ao ser injetada na circulação plasmática e adquire a apoE, que pode ser reconhecida pelo rLDL.…”
Section: Ldl Como Agente Direcionador De Fármacosunclassified